Prevalence of diabetic retinopathy in type 2 diabetic patients at Tertiary Hospital, Bangalore, India. - Devatha, Suresh; Preethi (International Journal of Medical Research and Review, 2024)
Diabetic retinopathy is a common microvascular complication seen in diabetic patients. The global prevalence is estimated to be 22.27 %.(1) Objective: The aim of this study was to assess the prevalence of diabetic retinopathy in type 2 diabetic patients visiting our institute – Karnataka institute of endocrinology and research. Furthermore, we evaluated the severity of diabetic retinopathy and factors associated with diabetic retinopathy like gender and age group. Methods: A total of 5,363 diabetic patients attending the vitreoretina OPD at our Institute from November 1st, 2022 to October 31st, 2023 were included in our study. Data was collected using a questionnaire and a detailed dilated examination was done by an ophthalmologist (vitreoretina specialist). Result: A total of 5,363 diabetic patients were included in the study.The prevalence of diabetic retinopathy was 30.84 % (95% CL: 29.66-32.12). Among 5,363 patients, 3705 patients had no diabetic retinopathy (69.15%), 812 had mild NPDR (15.14%), 438 had moderate NPDR (8.16%), 152 had severe NPDR (2.83%) and 252 patients had PDR (4.69 %). The prevalence of diabetic retinopathy was higher in males (34.82%) compared to females (25.01%). The odds ratio was 1.60. The prevalence of diabetic retinopathy was higher in age group above 45 years. Conclusion: The prevalence of diabetic retinopathy in our study was 30.84%, higher than global figures. Screening of all diabetic patients regularly and good glycemic control should be an integral part of diabetic care management to reduce the burden of diabetic retinopathy.